The Nationalism Practice of Chinese Ethnic at Pecinan Bintoro Village Demak Regency - Dewi, Lutfia Kusuma; Pramono, Suwito Eko; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2018)
Chinese ethnic in Pecinan Bintoro Demak is an Indonesian citizen who should have a sense of nationalism. The purpose of this study is to describe and analyze the understanding and form of participation in ethnic Chinese ethnic practices. The research method used qualitative approach with data collection technique through interview, observation, and document study. Interviews and observations were used to analyze ethnic Chinese understanding, while the forms of participation used interviews, observations, and document studies.The result of the research shows that (1) Chinese ethnic Pecinan Bintoro of Demak Regency have a unity meaning where society is united without seeing the difference of tribe, religion, culture, and all live together side by side. The family has a central role in instilling the values ​​of nationalism. (2) The form of ethnic Chinese participation is seen from the participation of ethnic Chinese in Kampung Pecinan Bintoro Demak District in several social activities, example salvation in commemorating Indonesia's independence day, and come to mourn when there are neighbors who died. Although for gotong royong activities, the competition on the anniversary of Agustusan is still not so visible, it does not make the boundary wall among the surrounding community.